Transparency of public private partnership (PPP): the extent of mandatory information disclosure - Ismail, Suhaiza; Shehu Musawa, Mubarak; Ahmad @ Abdul Mutalib, Hawa (2019)
Purpose – The purpose of this paper is to examine the extent public listed construction firms in Malaysia disclose mandatory information on public private partnership (PPP) projects. This paper is important as the level of disclosure of PPP information reflects the extent of transparency as practiced by the companies involved in PPP projects.